200 mm Ge Wafer Production for Oxide-Free Si-Ge Direct Wafer Bonding. (8th September 2020) - Rebhan, Bernhard; Vanpaemel, Johannes; Dragoi, Viorel
Abstract : Dislocation-free 200 mm diameter germanium wafers were manufactured via Czochralski crystal growth technique. Standard silicon wafers were used to demonstrate the feasibility of oxide-free Ge direct wafer bonding at room temperature. First the native oxides from both wafer surfaces were removed using ion beam sputtering, followed by the transfer of both wafers in ultra-high vacuum to the bonding process station in order to avoid re-oxidation. Subsequently annealing to correct for the sputter-induced amorphization was studied. For the qualification of the process the main focus was on the morphological and elemental analysis of the surfaces and of the bonded interfaces.